A tailored rhomboid mucocutaneous advancement flap to treat anal stenosis. (10th June 2020) - Gallo, G.; Stratta, E.; Realis Luc, A.; Clerico, G.; Trompetto, M.
Abstract: Aim: Anal stenosis (AS) is a rare but disabling disorder that often represents a complication of anorectal surgery. The aim of our study was to assess the safety and functional outcome of a modified rhomboid flap (MRF) in the treatment of moderate and severe AS. Methods: Between January 2002 and September 2017, 50 consecutive patients with moderate and severe AS who underwent an MRF were retrospectively included. Anal continence (Cleveland Clinic Incontinence Score) and symptoms (Obstructed Defaecation Syndrome Score) were assessed preoperatively and postoperatively at 12 months. Furthermore, anal calibre was measured both preoperatively and postoperatively at 1, 6 and 12 months. Results: The mean follow‐up period was 97 ± 48.3 (33–180) months. The main aetiology was a previous excisional haemorrhoidectomy ( N  = 23; 46%). The mean preoperative anal calibre was 9.96 ± 2.68 (5–15) mm and there was a statistically significant improvement in all three periods ( P  < 0.0001) of postoperative evaluation (1, 6 and 12 months) with a mean difference, obtained comparing preoperative and 12 months anal calibre, of 14.1 ± 2.72 ( P  < 0.0001). Statistically significant improvement in both Cleveland Clinic Incontinence Score and Obstructed Defaecation Syndrome Score was observed in all patients at 12 months. The overall success rate was 96% (48/50 patients). Conclusion: The use of an MRF is a safe and suitable option for the treatment of moderate and severe AS. The possibility of tailoring the flap, based on the degree as well as the level of AS, is the key.